Maternity Nurses' Responses to Maternal Early Warning Criteria. Issue 1 (January 2021) - Gillespie, Kate H.; Chibuk, Amber; Doering, Jennifer; Nelson, Ken
Abstract: Objective: The purpose of this study was to assess the influence of nursing care on implementing perinatal risk-appropriate care in the context of maternal early warning criteria. Design: Medical record review and survey of maternity nurses in a three-hospital system in Wisconsin with two level I hospitals and 1 level III hospital. Participants: Seven maternity nurses from the level III hospital conducted the medical record reviews and all maternity staff nurses from two level I hospitals were invited to complete the survey. Measurements: All medical records in 2017 that met these inclusion criteria: hypertension, sepsis, preeclampsia, hemorrhage, low Apgar scores, and transport were reviewed to assess identification and response time for maternal early warning signs using the Nurses Contribution to Maternal Mortality Worksheet . The survey included questions about influences on the nurses' confidence when interpreting early warning indicators. Results: Thirty-two medical records met inclusion criteria and were reviewed. The number of maternal early warning signs recorded ranged from one to four, with a mean of 1.75 indicators. Eighty percent of records documented increased evaluation as a nursing response to the maternal early warning signs. Time-lapse between notifying a provider and bedside evaluation was less than 15 minutes in 54% of cases. Of the 31 eligible nurses, 18 completed the survey (58% response rate). Personal knowledge (90%) was reported by nurses as being the greatest influence on nursing confidence. Sixty-nine percent of nurses reported not receiving patient information from team members at the transporting hospital. Conclusion: A systematic record review by frontline nurses can monitor identification and response to maternal early warning signs. Feedback on patient transports can reinforce nurses' decision-making that has the potential to improve responsiveness to clinical warning signs. Abstract : As the health care profession that provides the majority of hands-on, direct bedside clinical care, nurses are often the first to notice subtle and potentially concerning changes in maternal condition. In this study of nurses in a three-hospital system, nurses' response to maternal early warning signs were evaluated.